ER-phagy mediates selective degradation of endoplasmic reticulum independently of the core autophagy machinery - Schuck, Sebastian; Gallagher, Ciara M.; Walter, Peter (Journal of cell science, 2014)
Skip to Next Section - Selective autophagy of damaged or redundant organelles is an important mechanism for maintaining cell homeostasis. We found previously that endoplasmic reticulum (ER) stress in the yeast Saccharomyces cerevisiae causes massive ER expansion and triggers the formation of large ER whorls. Here, we show that stress-induced ER whorls are selectively taken up into the vacuole, the yeast lysosome, by a process termed ER-phagy. Import into the vacuole does not involve autophagosomes but occurs through invagination of the vacuolar membrane, indicating that ER-phagy is topologically equivalent to microautophagy. Even so, ER-phagy requires neither the core autophagy machinery nor several other proteins specifically implicated in microautophagy. Thus, autophagy of ER whorls represents a distinct type of organelle-selective autophagy. Finally, we provide evidence that ER-phagy degrades excess ER membrane, suggesting that it contributes to cell homeostasis by controlling organelle size.